Quantitation of polysorbate 80 in recombinant protein formulation using high-performance liquid chromatography - A. D. Askretkov; D. O. Shatalov; N. V. Orlova; D. I. Zybin; V. V. Nikolaeva; A. A. Klishin; E. S. Tuzova; D. S. Minenkov; S. A. Kedik; Yu. A. Seregin (Тонкие химические технологии)
Objectives. Polysorbate 80 (PS80) quantification in biopharmaceutical products has always been challenging owing to its minute content, absorption to the protein backbone, lack of specific chromophoric PS80 groups, and heterogenic nature. This work is aimed at developing an express method for PS80 analysis in biopharmaceutical products using hydrolysis and subsequent highperformance liquid chromatography analysis with ultraviolet detection that does not consume substantial amounts of sample (≥35 μL).Methods. Five therapeutic protein formulations were chosen as model proteins. Alkaline hydrolysis formulation was applied, without protein precipitation and with a range of precipitation techniques to remove protein from the test solution and hydrolyze PS80, to free fatty acids. The obtained hydrolysate was analyzed using reverse-phase high-performance liquid chromatography.Results. As a result of the high protein content of monoclonal antibody formulations, preliminary protein removal was required, which was achieved by precipitation with organic solvents. A specific precipitant ethanol–isopropanol mixture (1:1 volumetric ratio) was developed to efficiently remove antibodies while keeping PS80 in the solution. The PS80 quantification method was developed for monoclonal antibody drugs. For three monoclonal antibody drug products (adalimumab, infliximab, and eculizumab), method validation was performed according to the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use, the United States Pharmacopeia, and the State Pharmacopeia of the Russian Federation guidelines.Conclusions. The optimal assay conditions for each group of recombinant monoclonal antibody substances were chosen. Protein precipitation with ethanol or ethanol–isopropanol mixtures before hydrolysis was introduced, allowing for a substantial reduction of sample to 35 μL or even less if PS80 content is higher than 0.05 mg/mL. Accelerated hydrolysis (90 min) is preferable to slow hydrolysis (4–18 h). Method validation for protein products such as adalimumab, infliximab, and eculizumab was demonstrated for the first time. Both methods were validated for each drug product. The coefficients of variation for method specificity and high precision were ≤6.0% for 3 analyses. The accuracy of the methods ranged from 96% to 109% for all of the tested drug products.